2020
DOI: 10.1177/2055102920954711
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviors and depression “among adolescents in Hanoi, Vietnam: A multilevel analysis of data from the Youth Risk Behavior Survey 2019

Abstract: This study described the prevalence of suicidal behaviors and depression among adolescents in Hanoi, Vietnam, and examines the associated factors. In 2019, a school-based survey was conducted in three high schools in Hanoi and 661 high students were included into the study. We found that the prevalence of 12-month suicidal thoughts, suicide plans, and suicide attempts were 14.2%, 5.5%, and 3.0% respectively. Notably, the depression score mean was 16.1±4.9, among major predictors of suicidal ideation. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
6
2
Order By: Relevance
“…In this study, there was a significant relationship between depression and suicidal ideation. This finding is in congruence with the previous study by Windfuhr et al 30 in UK, Nguyen et al 31 in Asian, and Kandel et al 32 in Columbia who reported that depressive symptoms are the congruence with the previous study by Windfuhr et al 30 in UK, Nguyen et al 31 in Asian, and Kandel et al 32 in Columbia who reported that depressive symptoms are the strongest predictors of suicidal ideation. This is not surprising because suicidal ideation is one of the features of major depression.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, there was a significant relationship between depression and suicidal ideation. This finding is in congruence with the previous study by Windfuhr et al 30 in UK, Nguyen et al 31 in Asian, and Kandel et al 32 in Columbia who reported that depressive symptoms are the congruence with the previous study by Windfuhr et al 30 in UK, Nguyen et al 31 in Asian, and Kandel et al 32 in Columbia who reported that depressive symptoms are the strongest predictors of suicidal ideation. This is not surprising because suicidal ideation is one of the features of major depression.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the prevalence of suicide attempts during the previous 12 months was 32.1% (33.3% for the males and 31.3% for the females), which was much higher than in previous studies based on the Mongolian GSHS of 2010 (8.7%) [ 10 ] and 2013 (10%) [ 11 ]. In addition, this result was also higher than the 12-month prevalence of suicide attempts in China (9.4%) [ 30 ], the Philippines (15.34%) [ 31 ], Vietnam (21.2%) [ 32 ], or Thailand (13.3%) [ 33 ], but lower than in the Solomon Islands (36.9%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a collectivistic culture, the individual exists in a matrix of relationships; therefore, both risk and protective factors are closely related to the quality of an individual’s relationship rather than one’s own ability to overcome challenges and achieve personal goals (Stewart et al., 2004). In this review, the included studies from Middle East, Africa, and Asia highlighted cohabitation with parents, having large number of siblings, a single‐parent family, loss of parents, family abuse, family conflict, poor family function, harsh parenting, and unsatisfactory peer relationships as significant risk factors for depression (Fatiregun & Kumapayi, 2013; Latiff, Tajik, Ibrahim, Abubakar, & Ali, 2016; Lin et al., 2008; Nalugya‐Sserunjogi et al., 2016; Nguyen Thi Khanh et al., 2020; Shaikh, Doke, & Gothankar, 2018). On the contrary, these relationship‐based risk factors were rarely or not reported in the included studies from Europe, North America, and Oceania.…”
Section: Discussionmentioning
confidence: 99%